ЈОVAN HADŽIĆ’S CIVIL PROCEDURE CODE DRAFT (1845) - Stanković, Uroš (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
The article sheds light on civil procedure code draft prеpared by renown Serbian lawmaker Jovan Hadžić in 1845. Contrarily to Hadžić’s work on producing civil code, his efforts to write civil procedure code are to a large extent obscure. Original text of the draft has not been found. Therefore, one is imposed to reconstruct it with the aid of auxiliary sources, among which the record kept by the commission tasked with revision of the draft, has prevailing significance. The author made an attempt to determine the structure of the draft, as well as the contents of its provisions as accurately as possible, wherein the remarks that the Commission had made were of most assistance.     Hadžić consigned his draft to the Prince Aleksandar Karađorđević on August 4th 1845. The Draft consisted of introduction and three parts. The introduction comprised of general provisions. Therein was stipulated principle of trial by written declaration, determined five kinds of courts before which civil procedure should occur and established vacatio legis.     The first and concviningly largest part of the Draft was most likely entitled “On principal litigations and litigation evidence” (“O parnicama glavnima i parničnim dokazatelstvima”). It included diverse rules, such as proceedings before peace courts, proceedings before district courts, ordinary course of litigation (i. e. rules in terms of filing a complaint, scheduling of hearings, subpoenas delivery, procurement of evidence, trial, bankruptcy proceedings, forms of evidence, presentation of evidence and deliberation of judgment), appellate procedure, new trial and enforcement procedure.      The third part subsumed the title named “likvidacija” (literally “liquidation”), whose contents is undeterminable on the basis of existing text of the draft, resolution of bankruptcy proceedings via settlement, resolution of regular litigations via settlement, title named “on special proceedings and advantages” (“o osobenom postupanju i blagodejanijama”), probably related to bankruptcy proceedings) and arbitration tribunal. Within the third part, one can find solely two short titles encompassing provisions on judge and attorney’s service.     The Prince forwarded consigned draft to State Council. Thereafter the Council established the Commission to revise the Draft on August 20th 1845. The Commission was made up of Stojan Simić, president of the Council (as the chairman of the Commission), state counselors Lazar Arsenijević Batalaka and Stojan Jovanović, the Council’s Secretary Jovan Marinović, Director of Prince’s Office Aleksa Janković, professor of law Maksim Simonović, secretary of Appellate Court Jakov Dimšić, secretary of Archdiocese Consistory Court Vasilije Lazić and secretary of Ministry of Justice Pavle Popović.     The Commission made numerous alterations in the original text of the draft. Several titles were repositioned (settlement in bankruptcy proceedings, special proceedings and advantages, settlement in regular litigations and unnamed first title of the second part, probably referring to recusal). Some other remained in the same place, but were completely altered (rules on peace courts and unnamed fourth title in the first part, provisions on liquidation and arbitration tribunals and the whole third part). Rules on enforcement of judgements were modified exclusive of several provisions. The Commission also passed a multitude of remarks on contents and style of the draft’s articles, whereas the first-mentioned were far more frequent. Only a few provisions did not undergo any modifications. By reason of considerable corrections had been made, the Commission decided that the draft should be reproduced and confined that task to Maksim Simonović, its most qualified member. Howsoever, it turned out to be overcomplicated due to excessive changes and inability to reproduce some titles in a fashion to regulate respective matters detailedly enough. Consequently, the Commission ordered Simonović to write an entirely new draft, which meant Hadžić’s draft was definitely rejected as the basis for future civil procedure code. Notwithstanding the rejection, Hadžić’s draft is a document of great importance for Serbian legal history. It may be considered the first complete civil procedure code draft prepared by an expert. Thus it serves as a link between antecedent Vasilije Lazarević’s draft and subsequent complete and fully conserved texts.